2022
DOI: 10.1101/2022.03.01.482581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholesterol in the cargo membrane reduces kinesin-1 binding to microtubules in the presence of tau

Abstract: Intracellular cargos are often membrane-bound and transported by microtubule-based motors in the presence of microtubule-associated proteins (MAPs). Whereas increasing evidence reveals how MAPs impact the interactions between motors and microtubules, critical questions remain about the impact of the cargo membrane on transport. Here we combined in vitro optical trapping with theoretical approaches to determine the effect of a lipid cargo membrane on kinesin-based transport in the presence of MAP tau. Attaching… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…4. Transport motors have additional functions which complicate their study: for example, they contribute to organelle morphogenesis ('14, 22, 29' in Figure 1 Karasmanis et al, 2018;Monroy et al, 2020;Banerjee and Gunawardena, 2023;Genova et al 2023;Li et al, 2023); (c) how transport can overcome physical barriers especially in narrow axons (Yu et al, 2017;Wang et al, 2020;images in Bowen et al, 2007); (d) Vesicular transport was shown to be fuelled by 'on-board' glycolysis (Figure 2; Zala et al, 2013;Hinckelmann et al, 2016;Yang et al, 2022a), but how ATP supply is ensured for the transport of other cargoes is not known (Chamberlain and Sheng, 2019).…”
Section: The Complex Machinery Of Axonal Transport In Axonsmentioning
confidence: 99%
“…4. Transport motors have additional functions which complicate their study: for example, they contribute to organelle morphogenesis ('14, 22, 29' in Figure 1 Karasmanis et al, 2018;Monroy et al, 2020;Banerjee and Gunawardena, 2023;Genova et al 2023;Li et al, 2023); (c) how transport can overcome physical barriers especially in narrow axons (Yu et al, 2017;Wang et al, 2020;images in Bowen et al, 2007); (d) Vesicular transport was shown to be fuelled by 'on-board' glycolysis (Figure 2; Zala et al, 2013;Hinckelmann et al, 2016;Yang et al, 2022a), but how ATP supply is ensured for the transport of other cargoes is not known (Chamberlain and Sheng, 2019).…”
Section: The Complex Machinery Of Axonal Transport In Axonsmentioning
confidence: 99%
“…In cells, teams of kinesin motors bind to and move individual cargos (Welte et al, 1998;Shubeita et al, 2008;Hendricks et al, 2012;Leidel et al, 2012;Rai et al, 2013). Experimental efforts to understand the dynamics of motor teams in vivo and, with increasing levels of complexity, in vitro have unraveled important questions relevant to cellular transport (Gross et al, 2002;Mallik et al, 2005;Martinez et al, 2007;Vershinin et al, 2007;Shubeita et al, 2008;Derr et al, 2012;Hendricks et al, 2012;Jamison et al, 2012;Leidel et al, 2012;Xu et al, 2012;Blehm et al, 2013;Rai et al, 2013;Arpag et al, 2014;Bergman et al, 2018;Arpag et al, 2019;Tjioe et al, 2019;Li et al, 2023). However, given the limitation of what is experimentally feasible, simulations and models have also contributed to understanding cargo dynamics in various geometries and under various conditions (Kunwar et al, 2008;Korn et al, 2009;Kunwar and Mogilner, 2010;Kunwar et al, 2011;Arpag et al, 2014;McLaughlin et al, 2016;Arpag et al, 2019;Jiang et al, 2019;Khataee and Howard, 2019;Ohashi et al, 2019;Wilson et al, 2019;Bovyn et al, 2021;Yadav and Kunwar, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Dr. Jing Xu (University of California, Merced) [12] will talk about the inhibitory effect of tau on kinesin-1-based transport amplified by cholesterol in the cargo membrane [13]. She describes the finding by saying that "Intracellular cargos are often membrane-bound and transported by microtubule-based motors (such as kinesin-1) in the presence of microtubule-associated proteins (MAPS).…”
mentioning
confidence: 99%